(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Acinetobacter baumannii (A. baumanii) has recently emerged as a major pathogen causing nosocomial infections in patients admitted to intensive care units with a surprisingly rapid acquisition of antibiotic resistance. Objective: To study the rate of occurrence of A. baumanii in different clinical samples and to investigate the association between biofilm formation and presence of ompA and bap genes in multi-drug resistance isolates. Methods: A total of 150 clinical samples were collected from (blood, sputum, urine, wound swab) during a period from the first of October 2017 to the end of March 2018 from Al-Imamein Al-Kadhimein City, Central Teaching Hospital of Pediatrics, Welfare Children Protection in Medical City and Al-Yarmouk Teaching Hospital and tested against 14 antibiotics by disc diffusion method. Quantitative microtiter plate assay was done for detection of biofilm formation. Polymerase chain reaction (PCR) was performed to detect ompA and bap genes. Results: There were 75 A. baumanii isolated from different clinical samples as follows: 41 from blood, 13 from wound, 12 from sputum and 9 from urine. The results of antimicrobial susceptibility test showed, high rate of resistance to Aztronem (94.7%) followed by Cefotaxime (89.3%), Cefepim (86.7%), Meropinem (86.7%), Ceftriaxone (86.7%), Ceftazidime (85%), Gentamicin (85%), and Piperacillin (82.7%) respectively. Moderate - to - low rate of resistance to Ciprofloxacin (78%), Impenim (46.7%), Levofloxacin (46%), Amikacin (44%), Tigacycline (42.3%) and Colistin (44%). The detection of biofilm formation showed that (52%) of isolate produce biofilm and the prevalence of ompA gene was 86.7% while the prevalence of Bap-gene was 34.7%. Conclusion: High frequency of A. baumannii infection was observed in different hospitals in Baghdad. More than half of the isolates were biofilm producer and there is highly significant association between the presence of bap gene and the biofilm formation but not with ompA gene. Keywords: Acinetobacter baumannii, ompA, Bap, MD Citation: Talib SS, Abdulrahman TR, Ali SH. Detection of some biofilm genes related with multidrug-resistant in Acinobacter baumannii isolated from clinical isolates. Iraqi JMS. 2018; 16(4): 430-438. doi: 10.22578/IJMS.16.4.11